The Effectiveness of EM4 Addition in the Biofilter Tanks to Reduce TSS and Ammonia in the Sago Industry Liquid Waste - Mila Suryani Pohan; Sampe Harahap; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractSago liquid waste is rich in TSS and amonia and thus need to be processed before being flown to environment. A study aims to reduce the TSS and amonia in that waste by using the biofilter that was added with EM4has been conducted in April-May 2019. There were 3 treatments applied, namely the addition of 17 ml, 20 ml and 23 ml EM4in the anaerob and aerob tanks, 3 replications. The waste was settled for 3 days in the anaerob and 3 days in the aerob tanks. The treated waste was then tested for TSS and ammonia concentrations. The treated waste was also used for rearing Oreochromis niloticus seedlings. Results shown that after being treated using the EM4enriched biofilter the TSS reduced into 80 – 32 mg/L and amonia 2,6329– 1,0420 mg/L. The survival of Oreochromis niloticus seedling reared in the treated waste was 86-93%. The best treatment to reduce the TSS was the addition of 20 ml EM4and the effectiveness was 99%, while that of the ammonia was 90%.It can be concluded that the addition of EM4to the biofilter tanks was able to reduce the TSS and ammonia in the sago industrial liquid waste. Keywords: Aerob tank, Anaerob tank, Effective microorganism 4, Oreochromis niloticus